Stiffness Improvement of Corrugated Metal Roofs through Cross-Sectional Geometry Modification - Zidan Yusron Wijanarko; Prasetiyo, Angger Bagus (Universitas Negeri Semarang, 2025)
Nowadays, many Indonesian commonly use metal trapezoidal corrugated roofs for their residential needs. Nevertheless, the roofs often deformed or failed due to heavy rains or storms, especially in tropical regions like Indonesia. Therefore, a new model was investigated and proposed in this research to enhance the stiffness-to-weight ratio of the roofs. Computational simulation was conducted to compare the existing and the proposed model of the roofs. The addition of some small folds in certain positions successfully increases the stiffness-to-weight ratio of the roof by 11.58% compared to the existing model.